Analisis Model-Model Pembelajaran yang Digunakan oleh Guru IPS di SMP Negeri Se-Kecamatan Sukorejo Kabupaten Kendal - Wicaksono, Panggih Nugroho; Purnomo, Arif (Universitas Negeri Semarang, 2021)
The results showed that (1) the social studies teacher at SMPN 1 Sukorejo and SMPN 2 Sukorejo used the discovery learning model, while the social studies teacher at SMPN 3 Sukorejo used a varied lecture learning model, (2) the teacher implemented it according to the analyzed learning model, and in the implementation process there are obstacles experienced by teachers and students, (3) the teacher reflects on the learning model by looking at the activeness of students and the results of test scores. Then the teacher made improvements to the social studies learning model by discussing among teachers, using the peer tutor model, utilizing technology, and book references from various sources.